Immobilization of CALB on activated chitosan: Application to enzymatic synthesis in supercritical and near-critical carbon dioxide - dos Santos, Jose C. S. (2017)
Enzymatic synthesis of fatty acid ethyl esters in supercritical and near-critical carbon dioxide using lipase B from Candida antarctica (CALB) immobilized onto chitosan is here investigated. The objective was to evaluate the operational parameters that influence the enzymatic esterification reaction between oleic acid and ethanol, conducted in supercritical carbon dioxide, as a route to produce ethyl oleate. Biocatalyst has been prepared through the immobilization of CALB by covalent bond using chitosan activated with glycidol, ethylenediamine (EDA) and glutaraldehyde as support. In order to determine the best operational conditions of the esterification reaction, an experimental design (23) was conducted to evaluate the effect of the following parameters: alcohol to oil molar ratios, reaction time and temperature. The maximum conversion was 46.9% at a temperature of 29.9 °C, ethanol to oleic acid molar ratio equal to 4.50:1, and a reaction time of 6.5 hours. Additionally, the removal of water from the medium, by using zeolite, promoted an increase in the conversion of oleic acid into ethyl esters. These results show that the combined use of supercritical carbon dioxide and zeolite favors the enzymatic esterification reaction, increasing the yields.